Research on Collision Adhesion Characteristics of Dense Medium Particles to Coal Surface in Dry Dense Medium Fluidized Bed - XI Tong; REN Yongxin; LI Yanjiao; LIU Chenmin; DONG Yani; DONG Liang (Taiyuan Ligong Daxue xuebao)
[Purposes] The dry fluidized-bed separation technology represents a significant advancement of the gas-solid two-phase theory within the domain of coal beneficiation. During coal separation in fluidized beds, the surface moisture of coal is transported and dispersed throughout the bed with gas flow and particle movement, resulting in particle agglomeration. Particle agglomeration refers to the accumulation of particles caused by fluid actions and dissipative interactions between particles, leading to an irregular mesoscale structure. Particle agglomeration can adversely affect fluidization quality, bed stability, density distribution, and product quality. [Methods] In this study, the collision and adhesion characteristics between heavy medium particles and the coal surface under wet conditions are investigated, focusing on the particle collision and adhesion processes. [Findings] The findings indicate that an increase in collision velocity corresponds to an increase in the normal restitution coefficient of the particles. Furthermore, under same humidity conditions and collision velocities, the restitution coefficient increases with larger particle sizes. The primary energy loss during particle-particle collisions in a wet fluidized bed is attributed to surface viscoelasticity loss and liquid bridge adhesion loss. As relative humidity increases, the adhesion loss caused by liquid bridge forces progressively rises, resulting in a significant decrease in the particle restitution coefficient. [Conclusions] The mechanism of particle agglomeration collision and adhesion is revealed from this work, providing a theoretical basis for controlling the agglomeration of particles in sorting fluidized beds, maintaining stable fluidization of the bed, and improving the sorting efficiency of fluidized beds.